Case Report: Bosworth Fracture-Dislocation managed by Closed Reduction and Conservative Treatment - Ji, Wan-Bo; Xu, Yao-Feng; Lu, Zhen (Frontiers in Surgery, 2022)
Bosworth fracture-dislocation is a rare type of ankle injury, which in the typical radiologic are overlap of distal tibia and ﬁbula in the anteroposterior view, posterior subluxation of the talus and syndesmosis dissociation in the lateral view, while in the CT scan, the ﬁbula was displaced behind the posterior edge of the ﬁbular notch (incisura tibiae), locked between the distal tibia and the displaced posterior malleolus fragment. Treatment can be challenging owing to the ignorance or failure of the initial reduction, resulting in an irreducible tibiotalar joint and tibiofibular syndesmosis reduction. To treat this complicated injury, emergent open surgery is always recommended for the first stage reduction to prevent adverse events. Successful closed reduction and conservative treatment of Bosworth fracture-dislocation is rare. This unique case presents a 25-year-old male with a Bosworth fracture-dislocation cured with closed reduction and U-shaped plaster splint. The patient was fully weightbearing and had no pain, and there were no limitations in the range of motion of the ankle and subtalar joints at 30 months of follow-up.